OPTIMIZATION OF DIGITAL LITERACY THROUGH STEM-BASED LEARNING - Saleh, Hairul; Nopitasari, Dian; Fadillah, Ahmad; Bilda, Westi; Haswati, Desty (FKIP Universitas Muhammadiyah Tangerang, 2025)
The purpose of this study is to analyze and describe students' digital literacy skills in STEM-based vector algebra courses using online learning. The participants in this study came from 30 students of the mathematics education study program at the Universitas Muhammadiyah Tangerang. The research method used is descriptive qualitative, with an instrument in the form of a digital literacy questionnaire using a likert scale. The results showed that the ability to do internet searching indicators got a score of 77.50 with high criteria, the ability to use hypertext direction guides got a score of 77.50 with high criteria, the ability to evaluate information content got a score of 78.50 with high criteria, and the ability to compile knowledge got a score of 74.50 with medium criteria. The results of the indicator's average analysis showed that student digital literacy has an overall average of indicators with a score of 76.87 with high criteria. This study recommends the use of digital devices and STEM approaches in the learning proces